Customer Satisfaction and Brand Loyalty in Fast Food Industry in Azerbaijan - Budagova, Tamilla (ADA University, 2020)
Changing lifestyle of people over the world during the recent period caused the generation of significant number of differences between the eating habits of different generations. One of the fastest growing parts of the food industry is the fast-food industry in which people are served with the quick food options with comparably cheaper prices compared to the other dimensions of the food industry. The revenue from the fast-food industry generates almost 50% of the total revenue of food industry in the developed countries (Warsi and Nisa, 2005). In the developing countries, the revenues from the fast-food industry also increase because of the changing lifestyle of people which becomes even busier. Azerbaijan is also among the countries where the size of the fast-food market grows in a high speed (rate). Changing social and family structure also affect the eating habits of the people in Azerbaijan. After the independence of the country in 1991 and the signing of the “Contract of Century” with the well-known giant oil companies, the development of the Azerbaijan economy started which made the economy of the country attractive for many foreign companies which increased the amount of Foreign Direct Investment (FDI) to the country. Figure 1 also shows that the amount of the FDI inflows increased to the economy of Azerbaijan since 1994. Foreign investors also targeted the food industry in Azerbaijan because of the fact that increased amount of GDP per capita in Azerbaijan was a signal of higher amount of revenues in this industry for them. As a result, a number of fast-food restaurants opened in Azerbaijan, especially in the capital city of the country – Baku. While these early companies achieved to generate profitability and revenue growth in Azerbaijan in a short period of time because of the low number of competitors in the market, during the last decade, the number of fast-food industry participants increased in Azerbaijan as mentioned by Kiladze (n.d.). According to Kiladze, the consumption of fast-food snacks increased sharply in Azerbaijan since 2002. Increased number of alternatives for the customers created a competitor threat in the market. The increase in the number of competitors imply the increase in the bargaining power of the customers which in turn increases the importance of customer satisfaction for the management of companies to protect the profitability and guarantee sustainable revenue flows (Eva &Cmakalova, 2015). In Azerbaijan, the competitive pressure on the fast-food companies was increased also by the domestic companies because of the relative easiness of the starting a business in food industry. However, these companies also faced different challenges created by the companies that have high level of market power in the economy. Taking into account that the competition in the food industry increases, it becomes even more important for fast food restaurants to pay more attention to their marketing campaigns. In this paper, the author’s aim is to analyze the current state of customer loyalty and customer satisfaction in fast food industry in Azerbaijan. The main motivation behind the chosen research topic is the lack of the information in the existing literature regarding the customer satisfaction and loyalty patterns in the overall market in Azerbaijan which can make the fast-food industry participants to follow in order to not lose their customers. Author is also interested in the role of the different types of marketing campaigns implemented for the attraction of the customers, their satisfaction, and loyalty and the role of the cheaper prices and discounts in the profitability of the fast-food industry of the country. Moreover, the Strategic Roadmap on the Key Sectors of the National Economy of Azerbaijan (2016) mentions the importance of the increase in the number and quality of the domestic restaurant chains especially for the development of the tourism and food industry in the country. Considering the importance of the number and the quality of the fast-food restaurants for the Azerbaijan economy and growth in the market, the author will try to analyze the current state of the customer satisfaction and customer loyalty in the fast-food industry in Azerbaijan and will address the main points for the future improvements
Keywords: Business; Fast food industry -- Azerbaijan.; Customer satisfaction -- Azerbaijan.; Brand loyalty -- Azerbaijan.